Vitamin D intake in Italian healthy subjects and patients with different pathological disorders - Nuti, Ranuccio; Gennari, Luigi; Cavati, Guido; Caffarelli, Carla; Frediani, Bruno; Gonnelli, Stefano; Laurentaci, Concetta; Mauro, Giulia Letizia; Malavolta, Nazzarena; Minisola, Giovanni; Punzo, Maria; Capozzi, Anna; et al. (Frontiers in Nutrition, 2025)
BackgroundVitamin D deficiency is recognized as a widespread public health issue, particularly among individuals with limited sun exposure or chronic diseases. While cutaneous synthesis provides most vitamin D, dietary sources remain essential, particularly in populations with restricted outdoor activity or poor dietary habits.MethodsThis cross-sectional study evaluated dietary vitamin D intake in 1,372 Italian adults (997 females, 375 males; aged 40–80 years) using a validated 14-day Food Frequency Questionnaire (FFQ). Participants included 429 (31.3%) healthy individuals and 943 (68.7%) patients with various pathological conditions. The study was conducted across different Italian regions between May 2023 and December 2024. Analysis of variance (ANOVA) was used to compare differences in vitamin D intake by age, sex, health status, education, occupation, and dietary patterns. Multivariate linear and logistic regression analyses were applied to identify independent predictors of daily vitamin D intake.ResultsVitamin D intake was low across the entire cohort, with daily means of 198.5 IU (females) and 246.7 IU (males), significantly below recommended levels. Intake decreased with age and was lower in patients than in healthy subjects. The lowest intakes were observed in patients with osteoporosis, renal, oncologic, and neurological conditions. Socioeconomic status and education level were significantly associated with intake levels. Vegetarians and vegans showed particularly low intake levels (152.1 and 83.6 IU/day, respectively). Multivariate regression revealed that male sex predicted higher intake (+44.1 IU/day), while Northern Italian residence (−53.0 IU/day), lower education (−39.2 IU/day), and vegetarian/vegan diets were independently associated with reduced intake. Logistic regression showed male sex was protective against very low intake (< 200 IU/day) (Odds ratio: OR 0.72), while Northern residence (OR 1.61), low education (OR 1.45), vegetarian (OR 1.86), and vegan diets (OR 3.89) increased risk. Age and chronic disease status were not significant independent predictors after adjustment.ConclusionThis study confirms extremely low vitamin D intake in Italian adults, especially in older adults and those with chronic conditions. Public health initiatives promoting vitamin D-rich diets, food fortification, and supplementation, especially for at-risk groups, are urgently needed to prevent hypovitaminosis D and its associated health consequences.